Graphene New Trends and Developments - Ebrahimi, Farzad (IntechOpen, 2015)
This book is a result of contributions of experts from the international scientific community working in different aspects of graphene science and applications and reports on the state-of-the-art research and development findings on graphene through original and innovative research studies. Through its seven chapters, the reader will have access to works related to the theory and characterization of various planar heterostructures and nanoplatforms based on graphene and also the Compton effect in graphene, while it introduces photoactive graphene from functionalization to applications and also the modeling and control of a smart single-layer graphene sheet. Besides, it presents reviews on the modeling, synthesis, and properties of graphene and graphene technology and its applications in electronic devices.